Hot‐air‐assisted radio frequency blanching of broccoli: heating uniformity, physicochemical parameters, bioactive compounds, and microstructure. (3rd February 2023) - Qing, Shuting; Long, Yangyang; Wu, Yiwen; Shu, Shumin; Zhang, Fei; Zhang, Yan; Yue, Jin
Abstract: BACKGROUND: Vegetables are often blanched before drying. The hot‐water blanching (HWB) of broccoli reduces quality and is environmentally harmful. In this work, hot‐air‐assisted radio frequency heating blanching (HA‐RFB) of broccoli was developed for use before further drying processes. Blanching sufficiency, heating uniformity, and heating rate during HA‐RFB were investigated to improve the product's physicochemical properties and texture. Suitable heating conditions were achieved when HA‐RFB was applied with hot air at 70 °C, with an electrode gap of 10.7 cm, using a cylindrical container for the broccoli. RESULTS: Under these conditions, the relative peroxidase activity in broccoli decreased to 3.26% within 117 s, with 13.45% of weight loss. In comparison with HWB broccoli, the products blanched by HA‐RFB preserved their texture, bioactive compounds, and microstructure better. The ascorbic acid, sulforaphane, and total glucosinolate content in HA‐RFB products were 251.1%, 131.9% and 36.7% higher than those in HWB broccoli, and HA‐RFB treatment led to a greater weight loss (13.45 ± 0.50%) than HWB (8.70 ± 1.70%), which is very helpful for the subsequent drying process. CONCLUSION: This study demonstrated that HA‐RFB could be a promising substitute for HWB to blanch broccoli and other flower vegetables, especially as a pretreatment in the drying process. © 2023 Society of Chemical Industry.